2009
DOI: 10.1007/s12603-009-0002-4
|View full text |Cite
|
Sign up to set email alerts
|

Minimal eating observation form: Reliability and validity

Abstract: The MEOF has satisfying validity and reliability. The earlier model of eating difficulties was confirmed (MEOF-I), and the model was slightly adjusted to a new model, MEOF-II. Providing eating assistance seems effective in preventing malnutrition (weight loss and BMI below limits), and is mainly provided to persons with ingestion difficulties. Difficulties with energy intake and appetite are not associated with eating assistance; indicating that those persons might need support of some other kind. This support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(97 citation statements)
references
References 13 publications
2
93
2
Order By: Relevance
“…But a previous study [13] found that staffs are good at providing eating assistance for patients with ingestion difficulties, and that these problems do not strongly contribute to undernutrition risk. It has also been found that energy problems are the single most important factor among the eating difficulties that contribute to undernutrition risk [12,13]. A better targeting of PE-food and oral supplements is perhaps the most important step to take, as it is well known that dietary supplementation is beneficial by means of for instance better values in anthropometric measures, decreased hospital stay and mortality [21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 92%
“…But a previous study [13] found that staffs are good at providing eating assistance for patients with ingestion difficulties, and that these problems do not strongly contribute to undernutrition risk. It has also been found that energy problems are the single most important factor among the eating difficulties that contribute to undernutrition risk [12,13]. A better targeting of PE-food and oral supplements is perhaps the most important step to take, as it is well known that dietary supplementation is beneficial by means of for instance better values in anthropometric measures, decreased hospital stay and mortality [21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 92%
“…MEONF-II includes an assessment of eating difficulties (according to the Minimal Eating Observation FormVersion II (MEOF-II) [8] , unintentional weight loss, either low BMI (<20 for 69 years or younger, or <22 for 70 years or older) or calf circumference <31 centimetres, and an additional assessment of the presence or absence of clinical signs of undernutrition [3] . MEONF-II yields a total score ranging from 0-8.…”
Section: Undernutrition Riskmentioning
confidence: 99%
“…It has been shown that by having students to participate in the research process their attitudes towards research gets more positive [6] and that their research skills improve [6,7] . We have involved undergraduate nursing students in actual research projects since 2005 [2,[8][9][10] . For example, in a small study were the students (n=42) were research collaborators in a nutrition study, 86% stated that they got improved understanding of research and 38% got increased knowledge about nutrition [11] .…”
Section: Introductionmentioning
confidence: 99%
“…The MEONF-II includes assessments of unintentional weight loss, low BMI/short calf circumference, and eating difficulties. The included eating difficulties (food intake, chewing/swallowing, energy/appetite) are based on the Minimal Eating Observation Form -version II (MEOF-II) [22] [23]. An additional assessment of the presence of clinical signs of undernutrition is also included [17].…”
Section: Instrumentsmentioning
confidence: 99%